Virtual reality therapy in special needs education.: From therapy to inclusion - Ardai, Evelyn; Vámos, Tibor; Papp, Gabriella; Berencsi, Andrea (Gyermeknevelés Tudományos Folyóirat, 2022)
The Virtual Reality (VR) technology has become a part of our everyday lives. The VR systems allow the users to be directly involved in human-computer interaction. The Virtual Environment provides artificial sensory information, while Virtual Tools allow direct interaction from the users side. Virtual devices such as computers, smartphones, and interactive whiteboards often appear both in general and special education. Education and rehabilitation professionals also use VR systems in various fields. The aim of the study is to summarise the wide range of VR system applications in diversified areas of special education. Our literature review focuses on special education and rehabilitation, moving towards the context of inclusion. Based on the numerous research, applying VR tools to the educational field has been increasing year by year. In the early ’90s, researchers began using virtual learning environments and they demonstrated that the application of virtual methods can be extended to behavioral therapies (relate anxiety), physical therapies (e.g. wheelchair simulators), and to develop cognitive performance (to develop attention) or social skills (learning to navigate community literacy). VR systems allow the possibility of providing continuous feedback and the opportunity for interactive learning and skill development. In the practice of special needs education, VR systems are useful in intervention, as well as monitoring, and evaluation. By using VR systems, users from any age group can be motivated. Furthermore, these systems apply their own natural semantics and can be used without spoken language or other conventional symbols. VR can promote education more accessible and differentiated for children with disabilities. This is one of the conditions for the effectiveness of co-education. The VR systems make no distinction between the users, on the other hand, users with special needs may require more adaptation or support in using VR. Hungarian professionals in the field of special needs education are also using VR tools, which offer opportunities to develop skills for independent living.